Respostas

2014-06-05T19:38:46-03:00
a) 3x - 3 - 4x - 2 = 6
   (passa os números para o outro lado)
  3x - 4x = 6 + 3 + 2
  -x = 11 .(-1)
  x = 11

b) 2x = -5 + 1
  2x = -4
 x = -4/2
 x = -2


c) 6x - 5x = 6 + 2 - 5
   x = 3

d) 4x - 3x = 5
  x = 5

2014-06-05T19:39:09-03:00
 a)3x-3 -4x -2 = 6       b) 2x -1 = -5

c)6x -2 +5 =5x +6     d)3x + x = 5 +3x


a) 3x - 3 - 4x - 2 = 6
 3x - 4x - 3 - 2 = 6
      - x - 5 = 6
      - x = 6 + 5
      - x = 11
        x = + 11

b) 2x - 1 = - 5
2x = - 5 + 1
2x = - 4
x = - 4/2
x = - 2

c)6x -2 +5 =5x +6  

 6x- 2 + 5 = 5x + 6
 6x + 3 = 5x + 6
6x - 5x = 6 - 3
x = 3


 d)3x + x = 5 +3x

  3x + x = 5 + 3x
      4x  = 5 + 3x
4x - 3x = 5
x = 5